Review procedure for death penalty in China: ‘Last Straw’ or a formality to the defendan? - Fu, Xin (Fakulti Undang - Undang, 2006)

(untitled)
Every human being has the inherent right to life. However, the death penalty is the severest penalty and deprives the convicted person of his life. Against the background of more and more countries abolishing the death penalty, it is necessary for China, the nation with the highest number of executions as reported by International Amnesty, to examine its policy on the death penalty. This article consists of four parts. Part One introduces the court system and the trial process in China, with a view to help understand the current practice of handling criminal cases. Part Two review the historical development of the review procedure for the death penalty in the People’s Republic of China since its foundation. Part Three examines the problems with the review procedure in practice. Part Four contains recommendations for the improvement of the review procedure. It is submitted that the power of reviewing death penalty cases (especially cases involving immediate execution) should be subject to ultimate decision by the Supreme People’s Court. On the basis that China is not yet ready to abolish the death penalty, it is argued that it should restrict the availability and review procedure of the death penalty, insist on fewer and more considered executions, prevent wrongful executions and thus better protect the human rights of defendants. Without these additional protections, the procedure can only be a formality in practice rather than the ‘last straw’ envisaged by law